200k views
5 votes
4-2/3(4x-9)=11 solve for x

User Shridhar
by
5.1k points

2 Answers

5 votes

Simplify both sides of the equation.

4 − 2/3 (4x − 9) = 11

4 + −8/3 x + 6 = 11

Distribute

(−8/3 x) + (4 + 6) = 11

Combine Like Terms

−8/3x+10=11

Subtract 10 from both sides.

−8/3x + 10 − 10 = 11 − 10

−8/3

x = 1

Multiply both sides by 3/(-8).

(3/−8)*(−8/3 x) = (3/−8)*(1)

x = −3/8



User Manuel Otto
by
5.6k points
6 votes

x= -3/8

here's how you solve it!

first distribute the -2/3 into the parentheses and you'll get:

4-8/3x+6=11

Then add 4 and 6 together

10-8/3x=11

Then multiply the equation by 3

30-8x=33

Then move the constant to the other side and change the sign

-8x=33-30

Subtract 30 from 33

-8x=3

Then divide both sides by -8

x=-3/8

Then you are left with your answer:

x= -3/8

Hope this helps! :3

User LJM
by
5.4k points